PENGARUH CAPITAL ADEQUACY RATIO (CAR) TERHADAP NET OPERATING MARGIN (NOM) DENGAN NON PERFORMING FINANCING (NPF) SEBAGAI VARIABEL INTERVENING PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2022-2024 - Aies Apriliza Seventin; Muhammad Ziyan El Haq; Ranti Novanda Eka Prawesti; Diah Ayu Anis Wulandari; Desti Tampi Prabowo; Achmad Miftachul Huda (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2026)
The Islamic banking industry in Indonesia shows promising growth, reflected in asset expansion and increased public trust in sharia-based financial systems. This study examines the effect of Capital Adequacy Ratio (CAR) on Net Operating Margin (NOM) with Non-Performing Financing (NPF) as an intervening variable in Indonesian Islamic Commercial Banks (Bank Umum Syariah/BUS) during 2022–2024. Using a quantitative associative-causal design with secondary data from 36 monthly observations sourced from OJK publications, the study employs simple linear regression, multiple linear regression, and path analysis. Assessment of classical regression assumptions comprising normality, multicollinearity, heteroscedasticity, and autocorrelation tests were all fulfilled. Results indicate that CAR has a significant negative effect on NPF (t = –8.082; Sig. = 0.000), CAR has a significant positive effect on NOM (t = 5.988; Sig. = 0.000), and NPF has a significant positive effect on NOM (t = 4.008; Sig. = 0.000). Path analysis reveals that NOM significantly mediates the relationship between CAR and NPF, with the indirect effect (–4.148) exceeding the direct effect (–1.035). These findings confirm that capital adequacy affects financing quality through the channel of operational profitability. Keywords:Capital Adequacy Ratio, Net Operating Margin, Non-Performing Financing, Islamic Banking, Path Analysis.